2015
DOI: 10.1002/anie.201506205
|View full text |Cite
|
Sign up to set email alerts
|

A Photonic Crystal Protein Hydrogel Sensor for Candida albicans

Abstract: We report two-dimensional (2D) photonic crystal (PC) sensing materials that selectively detect Candida albicans (C. albicans). These sensors utilize Concanavalin A (Con A) protein hydrogels with a 2D PC embedded on the Con A protein hydrogel surface, that multivalently and selectively bind to mannan on the C. albicans cell surface to form crosslinks. The resulting crosslinks shrink the Con A protein hydrogel, reduce the 2D PC particle spacing, and blue-shift the light diffracted from the PC. The diffraction sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
106
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(107 citation statements)
references
References 45 publications
0
106
0
1
Order By: Relevance
“…Each intermediate state exhibits a specific and easily perceived diffractive color, which can be used as a colorimetric indicator of the analyte concentration. In sharp contrast to most state‐of‐the‐art photonic crystal sensors, the multiple temporary configurations of the SMP‐based chromogenic sensors are structurally fixed and can be stored under ambient conditions for a long period of time. These “frozen” intermediate states enable reliable optical and microstructural characterization of the SMP membranes at any time interval during the reversible SM cycle, which greatly facilitate fundamental mechanistic studies on intriguing nanoscopic SM effects and swelling dynamics of macroporous SMP membranes with complex hierarchical porous networks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each intermediate state exhibits a specific and easily perceived diffractive color, which can be used as a colorimetric indicator of the analyte concentration. In sharp contrast to most state‐of‐the‐art photonic crystal sensors, the multiple temporary configurations of the SMP‐based chromogenic sensors are structurally fixed and can be stored under ambient conditions for a long period of time. These “frozen” intermediate states enable reliable optical and microstructural characterization of the SMP membranes at any time interval during the reversible SM cycle, which greatly facilitate fundamental mechanistic studies on intriguing nanoscopic SM effects and swelling dynamics of macroporous SMP membranes with complex hierarchical porous networks.…”
Section: Resultsmentioning
confidence: 99%
“…The visually perceived color changes associated with stimuli‐responsive PBG shifts in active photonic crystals have also been extensively exploited as a more convenient transduction mechanism than traditional electrical pathways for developing novel, low‐cost chemical sensors . Various photonic crystal geometries ranging from mesoporous 1D Bragg stacks and 2D photonic crystal fibers to 3D inverted photonic crystals and porous silicon membranes, coupled with many stimuli‐responsive materials, such as hydrogels (including those with specific analyte‐binding ligands), oxides, semiconductors, metals, and polymers, have enabled sensitive colorimetric and/or spectroscopic detection of a large variety of chemical and biological analytes (e.g., glucose, proteins, metal ions, alcohols, and water) . Drastic color shifts of photonic crystal sensors are commonly achieved through changes in lattice constants (for example, induced by swelling/deswelling of hydrogels) and/or effective refractive indices (e.g., caused by liquid uptake in porous photonic crystals) .…”
Section: Introductionmentioning
confidence: 99%
“…They made use of the shrinking of the hydrogel when exposed to the pathogen to modify the particle spacing in the 2D array, which translated to visually evident blue shifts of diffracted light that could be readily detected. The sensor is a proof of concept for utilizing recognition between microbial cell surface carbohydrates and lectins to detect microorganisms in aqueous environments [159]. Men et al reported that optical sensors based on hydrogel films with 2D colloidal arrays on both surfaces exhibited enhanced diffraction intensity and avoided the curling problems on traditional hydrogel films with only a single colloidal array on one side [160].…”
Section: Sensorsmentioning
confidence: 99%
“…Inverse opals (IOs), featuring a 3D ordered interconnected pore system with extremely uniform pore size, have received great attention owing to their wide applications in photonic crystals, sensors, dye‐sensitized solar cells (DSSCs), catalysis, etc. Normally, a colloidal crystal obtained by self‐assembly of microspheres is employed as template for the infiltration of metal oxides, carbon, polymer, conducting polymers, etc., and after the removal of the microspheres IOs of corresponding materials could be obtained.…”
Section: Introductionmentioning
confidence: 99%